COMPARISON OF PSORALEN ULTRAVIOLET A (PUVA) PHOTOCHEMOTHERAPY PLUS TOPICAL CORTICOSTEROIDS WITH PUVA PLUS BLAND EMOLLIENTS IN THE TREATMENT OF PSORIASIS - Tahir, Raheel; Mujtaba, Ghulam (Journal of Ayub Medical College Abbottabad, 2005)
Background: Psoralen Ultraviolet A (PUVA) therapy is a well-established treatment of psoriasis. The objective of the study was to compare the clinical improvement in psoriasis with PUVA photochemotherapy + topical corticosteroids and PUVA + bland emollients. Methods: Forty patients with chronic plaque type of psoriasis were divided into two equal groups each having 20 patients. PUVA therapy was given thrice weekly. In addition, patients of group-A were allowed to apply topical betamethasone 17-valerate 0.1% diluted 1 into 2 parts with plain vaseline twice daily. Patients of group-B were allowed to apply only plain vaseline over lesions twice daily. Clinical improvement in lesions was observed by decrease in the severity of erythema, scaling and plaque elevation. Results: Clearance of psoriasis was achieved in 95% of the patients treated with PUVA plus topical corticosteroids while clearance was achieved in 80% of patients treated with PUVA plus bland emollients (P=0.0758). Median numbers of exposures for group-A were 16 & for group-B were 17.5 (p= 0.1029). Similarly, median cumulative dose in group-A was 64.5 J/cm2 & in group-B was 70.7 J/cm2 (p= 0.372). Conclusion: There is no significant difference in clinical improvement in psoriasis treated either by PUVA plus topical steroids or PUVA plus bland emollients. Key Words: Psoriasis, PUVA therapy, Betamethasone 17-valerate, Emollients